Business Innovation for SMEs and Community Empowerment: Strategies to Enhance Income and Quality of Life - Arjang; Junaidi, Ahmad; Choerudin, Achmad (Tirakat: Jurnal Terobosan Peduli Masyarakat, 2024)
Small and Medium Enterprises (SMEs) play a crucial role in a country's economy. In the era of globalization and digitalization, SMEs need to innovate to remain competitive. This is because SMEs often face various challenges that hinder their business growth and sustainability. This research aims to explore business innovation strategies that can be applied by SMEs and how community empowerment can support the increase of income and quality of life. This research is a literature review with a qualitative approach and descriptive analysis. Descriptive analysis is used to describe and summarize findings from articles collected from Google Scholar for the period 2001-2024. The results of the study indicate that in the constantly changing economic dynamics, business innovation is key to the sustainability and advancement of SMEs. Although SMEs play a vital role in the economy, they often face challenges such as limited resources, access to capital, and lack of awareness of the importance of innovation in facing increasingly fierce global competition. To address these challenges, community empowerment and business innovation development become essential strategies. Therefore, recommendations from this study include enhancing community empowerment through training, education, and access to resources to create an environment that supports SME growth and leveraging ICT to improve operational efficiency and expand SME market reach.